Twelve Antioxidant Peptides From Protein Hydrolysate of Skipjack Tuna (Katsuwonus pelamis) Roe Prepared by Flavourzyme: Purification, Sequence Identification, and Activity Evaluation - Wang, Jiao; Wang, Yu-Mei; Li, Long-Yan; Chi, Chang-Feng; Wang, Bin (Frontiers in Nutrition, 2022)
For using aquatic by-products to manufacture high-value products, Skipjack tuna (Katsuwonus pelamis) roes were degreased, pretreated with microwave, and hydrolyzed using five protease. The protein hydrolysate (TRPH) generated using Flavourzyme displayed the strongest 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. Twelve antioxidative peptides were prepared from TRPH by ultrafiltration and chromatography methods and determined to be SGE, VDTR, AEM, QDHKA, TVM, QEAE, YEA, VEP, AEHNH, QEP, QAEP, and YVM with molecular weights of 291.24, 489.50, 349.41, 597.59, 349.44, 475.42, 381.36, 343.37, 606.58, 372.35, 443.42, and 411.49 Da, respectively. AEM, QDHKA, YEA, AEHNH, and YVM presented the strongest scavenging activity on DPPH radical (EC50 values of 0.250±0.035, 0.279±0.017, 0.233±0.012, 0.334±0.011, and 0.288±0.015 mg/mL, respectively), hydroxyl radical (EC50 values of 0.456±0.015, 0.536±0.021, 0.476±0.051, 0.369±0.052, and 0.413±0.019 mg/mL, respectively), and superoxide anion free radical (EC50 values of 0.348±0.018, 0.281±0.013, 0.305±0.022, 0.198±0.011, and 0.425±0.021 mg/mL, respectively). Moreover, AEM, QDHKA, YEA, AEHNH, and YVM presented high lipid peroxidation inhibition ability, Ferric-reducing power, and significant protective function on H2O2-induced Chang liver cells. Therefore, AEM, QDHKA, YEA, AEHNH, and YVM could be natural antioxidant ingredients used in pharmaceutical and functional products.